PRACTICAL EXAMPLES ON BIM-GIS INTEGRATION BASED ON SEMANTIC WEB TRIPLESTORES - Schilling, S.; Clemen, C. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2022)
The integration of geodata and building models is one of the current challenges in the AECOO (architecture, engineering, construction, owner, operation) domain. Data from Building Information Models (BIM) and Geographical Information Systems (GIS) can’t be simply mapped 1:1 to each other because of their different domains. One possible approach is to convert all data in a domain-independent format and link them together in a semantic database. To demonstrate, how this data integration can be done in a federated database architecture, we utilize concepts of the semantic web, ontologies and the Resource Description Framework (RDF). It turns out, however, that traditional object-relational approaches provide more efficient access methods on geometrical representations than triplestores. Therefore we developed a hybrid approach with files, geodatabases and triplestores. This work-in-progress-paper (extend abstract) demonstrates our intermediate research results by practical examples and identifies opportunities and limitations of the hybrid approach.